Actual Risks In the International Tourist Activity - Bednarska, Olha; Kulynyak, Ihor (Видавництво Львівської політехніки, 2013)
In the article actual risks and their factors are identified in the international tourist activity. On the basis of specific classification signs, the classification of risks is improved in the international tourism. The methods of optimization of risks are described.
Keywords: international tourism; risks; factors of risks; riskmanagement; optimization methods of risks; insurance